The Role Of Social Capital On Msme Performance Through Innovative Work Behavior - Priyo Utomo; Sri Wartini (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The purpose of this study was to examine the effect of social capital on MSME performance through innovative work behavior. The population of this research is the owners of culinary MSMEs in Semarang City. Based on slovin calculation, a sample of 100 respondents was obtained and data collection using purposive sampling. The data analysis method used is validity and reliability test, descriptive analysis test, and hypothesis testing using Structural Equation Mode (SEM) with SmartPLS version 4.0 analysis tool. The results showed that social capital affects innovative work behavior and MSME performance both directly and indirectly. This is supported by the role of innovative work behavior variables in mediating the relationship between social capital and MSME performance. Suggestions for further research should add or combine with other predictor variables so that research can be generalized such as knowledge sharing, and entrepreneurial leadership to improve MSME performance.